The waste management CBC projects in environmental cooperation between Finland and Russia : a case study of waste management projects in Karelia CBC Programme - Goljakov, Kristina (Helsingin yliopisto, 2021)
The main task of this thesis is to investigate the Finnish-Russian collaboration in the field of the environment, and more specifically, in the field of waste management. The history of Finnish-Russian cooperation goes back to more than one decade. This cooperation has always been influenced by the political situation in these two neighboring countries. The need for collaboration is also motivated by the necessity to solve mutual problems, such as can be seen in the field of environmental protection. However, since Finland's accession to the European Union, the relationship between these two countries has gained a new overtone. This study aims to answer to the main research question “What do the experiences gained in Finnish-Russian waste management projects reveal about the environmental cross-border cooperation between Finland and Russia?”, and to the sub-questions: “What are the benefits and/or opportunities project participants are searching for?” and “What kind of challenges can be found during project implementation?”. Such formulation of the research task enables to enrich comprehension of cross-border cooperation between Finland and Russia and its potential in the future. The analysis of particular case study promotes better understanding of how the CBC waste management projects work, what challenges can be met during the project implementation, and what risks should be accounted for in the future. In this research, the method used for data collection is questionnaire. This enabled to choose a particular approach for the analysis that was based on Miles and Huberman’s model of qualitative content analysis. The data consisted of replies from five respondents who were also actively involved in two different CBC waste management projects conducted under the framework of the Karelia CBC Programme. Their answers helped to evaluate and analyze the expected and unexpected issues that can be met during project implementation, as well as benefits these projects brought to the countries they represented. The ...